2015
DOI: 10.4103/2231-0754.153494
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices of interdental aids among medical professionals in Davangere district, Karnataka

Abstract: Objectives:The purpose of this study was to evaluate awareness regarding interdental aids in medical population. Materials and Methods: This study included 337 medical professionals living in Davangere district, Karnataka, India. A dental health questionnaire was distributed to all subjects consisting of 18questions. Results: Total 337 people with 187 females and 150 males who were of mean age 27.6±9.0 years participated in the study. The signifi cant positive response (<0.05) in females as compared to males w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
(35 reference statements)
2
3
0
Order By: Relevance
“…3,16 This is due to poorer oral hygiene, less positive attitude towards oral health, and dental-visit behavior among males than to any genetic factor. 17 In this study, gender and knowledge level of the participants was found to be statistically insignificant which is similar to the study conducted by Taani 13 and Vandana et al 18 but is in contrast to other studies. 12,19,20 Periodontal disease increases with increase in age.…”
Section: Discussionsupporting
confidence: 81%
“…3,16 This is due to poorer oral hygiene, less positive attitude towards oral health, and dental-visit behavior among males than to any genetic factor. 17 In this study, gender and knowledge level of the participants was found to be statistically insignificant which is similar to the study conducted by Taani 13 and Vandana et al 18 but is in contrast to other studies. 12,19,20 Periodontal disease increases with increase in age.…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings have been reported by Vandana et al (2015), where they mentioned that oral hygiene measures involving interdental aids are not common among medical under graduates.…”
Section: Introductionsupporting
confidence: 87%
“…It was further seen in the present study that a significant association was present regarding the awareness of interdental cleaning and oral hygiene practice among both genders while in a study by Vandana et al, it was observed that girls were more concerned about the maintenance of oral hygiene in comparison to boys. 15 The most frequently used interdental aid in the present study was seen to be toothpicks in 46.8% of medical students followed by the usage of dental floss in 25% to clean the interdental area while in a study in India, it was observed that 2% of the participants used dental floss regularly while 18% were seen to use it occasionally. 18 The usage of interdental aids in medical students showed that most of them were aware of their usage for cleaning interproximal surfaces.…”
Section: Discussionmentioning
confidence: 42%
“…Information regarding oral hygiene maintenance is fundamental in promoting self-prevention as one of the leading causes of gingivitis and periodontitis is plaque. [15][16] It has been reported that flossing in addition to tooth brushing is imperative in controlling the amount of dental plaque. 15 Therefore, the present study was planned to raise awareness regarding the usage of interdental aids in conjunction with tooth brushing among the medical students of district Sheikhupura.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation